Social Reintegration Model For Juvenile Prisoners: An Indonesian Perspective - Rinaldi, Kasmanto (Jurnal Dinamika Hukum, 2024)
Juvenile recidivism poses significant challenges for society, as young offenders often cycle through crime due to negative environmental influences and lack of support. This study aims to explore effective rehabilitation strategies for juvenile recidivists in Pekanbaru, Indonesia. Data were collected through interviews with juvenile inmates, prison guards, and analyses of inmate files, guidance regulations, and annual reports. The findings indicate that a comprehensive coaching model, which includes rehabilitation, educational initiatives, social support, and legal education, significantly aids in the social reintegration of juvenile offenders. The study highlights the importance of tailored rehabilitation approaches that address the unique needs of juveniles compared to adult offenders. To enhance reintegration efforts, the author recommends implementing community-based support programs and increasing collaboration between juvenile justice systems and local organizations to provide ongoing assistance and mentorship for former inmates.Keywords: Juvenile recidivism, recidivism, recidivist, recidivist coaching, social reintegration.